Estimation of screening sensitivity and sojourn time from an organized screening program. (October 2016) - Jiang, Huan; Walter, S.D.; Brown, P.E.; Chiarelli, A.M.
Highlights: A procedure is proposed to model the pre-clinical disease state duration, the false negative rate of the screening exam, and the underlying incidence rate in the screened population. Our results suggest that the mean preclinical duration is longer than 2 years. We also find only small marginal gains by screening every two instead of three years. Abstract: Regular screening with mammography is widely recommended to reduce breast cancer mortality. However, whether breast screening does more harm than good has long been debated. Since a full evaluation of the effect on mortality could take 10–15 years in order to provide a reliable estimate of the eventual benefits and harms, it is unrealistic to expect each new modification of a screening technique to be evaluated in this way. Therefore, one needs to rapidly estimate suitable measures of the screening effect. In this paper, two measures of interest, the length of the pre-clinical state and the screening false negative rate, are discussed. A procedure is proposed to model the pre-clinical disease state duration, the false negative rate of the screening exam, and the underlying incidence rate in the screened population. We applied the model to data from the Ontario Breast Screening Program in Canada. Our results suggest that the mean preclinical duration is longer than 2 years. We also find only small marginal gains by screening every two instead of three years. The most important objective of a screening program should be to encourage first-time screening attendance.